2021
DOI: 10.1007/s11557-021-01743-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic characterization and antimicrobial properties of Induratia species isolated from Coffea arabica in Brazil

Abstract: Fungi belonging to the genus Induratia are endophytes that have received considerable attention because of the production of natural bioactive secondary metabolites, such as volatile compounds, with antimicrobial activity. In this study, we distinguished I. coffeana and Induratia sp. isolated from Coffea arabica in Brazil based on three-loci phylogeny, ITS, RPB2, and TUB2. The Induratia isolates showed high morphological plasticity and produced different volatile organic compounds, indicating that these compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…(CML 4013) were isolated from healthy fresh leaves and stems of coffee plants (Coffea arabica). The plants were growing spontaneously in a secondary forest in Mata do Paraíso (20° 48′ 03.4″ S, 42° 51′ 42.6″ W), Zona da Mata region, Viçosa, Minas Gerais, Brazil (Guimarães et al 2021).…”
Section: Endophytic Fungimentioning
confidence: 99%
See 3 more Smart Citations
“…(CML 4013) were isolated from healthy fresh leaves and stems of coffee plants (Coffea arabica). The plants were growing spontaneously in a secondary forest in Mata do Paraíso (20° 48′ 03.4″ S, 42° 51′ 42.6″ W), Zona da Mata region, Viçosa, Minas Gerais, Brazil (Guimarães et al 2021).…”
Section: Endophytic Fungimentioning
confidence: 99%
“…The various metabolites, volatile or not, produced by the fungi of the genus Induratia (e.g., alcohols, amines, acids, esters, ketones, and some hydrocarbons) can perform hormonal, antibiotic, antitumor, antidepressant, antifungal, cytotoxic, antiviral, immunosuppressive, antiparasitic, and antioxidant activities (Kusari and Spiteller 2011;Strobel 2014;Demain 2014;Meshram et al 2014;Saxena et al 2015;Li et al 2018;Kaddes et al 2019). VOCs produced by Induratia yucatanensis (as Muscodor yucatanensis) showed lethal effects against different phytopathogenic fungi as Guignardia mangiferae, Colletotrichum sp., Phomopsis sp., Alternaria solani, Rhizoctonia sp., Phytophthora capsici, P. parasitica, Botrytis cenerea, Rhizoctonia solani, and Cercospora coffeicola (Macías-Rubalcava et al 2010;Monteiro et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Penicillium digitatum(Pena et al, 2019), Botrytis cinerea(Guimarães et al, 2021), Colletotrichum lindemuthianum, Sclerotinia sclerotiorum, and Pseudocercospora griseola(Mota et al, 2021) Gomes et al (2023). showed that Muscodor coffeanum isolates from coffee plants presented antimicrobial activity against Aspergillus ochraceus, A. sclerotiorum, A. elegans, A. foetidus, A. avus, A. tamari, A. tubingensis, A. sydowii, A. niger, A. caespitosus, A. versicolor, and Penicillium expansum, In addition, M. coffeanum showed nematicidal activity against Meloidogyne incognita and antibacterial activity against Staphylococcus aureus, Enterococcus faecalis, and E. faecium, and even reduced preformed bio lms of Staphylococcus aureus and Staphylococcus epidermidis…”
mentioning
confidence: 99%